The Promotion of Sustainability Policy in the Urban Context: the Role of Industrial Companies - Mura, Giulia; Aleotti, Francesco; Diamantini, Davide (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Many medium-sized Italian cities share the problem of having incorporated or having to integrate within the urban area relevant industrial components that influence both the overall quality of life and the environment in a strict sense. Sustainability perspectives are a relevant starting point for guiding companies’ development and growth strategies. At the same time, this aspect constitutes a strategic opportunity for urban development, that is still conditioned by the direct presence of companies that, in the best scenario, simply comply with current regulations in term of sustainability. The classic stakeholder theory, which is widely diffused in organizational culture, must be revised to solidify the understanding of the role of local stakeholders, who are passively involved in the environmental impact of companies’ activities. Studying the awareness, among the different corporate components, of environmental issues, is a very relevant step to trigger processes of effective improvement. In this article, we would like to argue that a greater understanding of sustainability issues on the part of decision-makers and employees of companies is a key that can have concrete effects on an aggregate level in the urban dimension. To verify this hypothesis, we propose a case study comparing three organisations, composed of ten plants spread across the Italian territory and all located in the proximity of medium-sized cities. Adopting a mixed qualitative-quantitative methodology, the work crosses primary qualitative data (semi-structured interviews with key players), quantitative data and secondary data relating to the territorial context. The results allow to highlight limits and potential of the industrial-urban coexistence, with a specific focus on the relation between private and public actors.